Changes in mean-squared charge radii and magnetic moments of 179-184TI measured by in-source laser spectroscopy - Barzach, A. E.; Fink, Daniel (Physical review, 2017)
Hyperfine structure and isotope shifts have been measured for the ground and isomeric states in the neutron-deficient isotopes 179-184Tl using the 276.9-nm transition. The experiment has been performed at the CERN-Isotope Separator On-Line facility using the in-source resonance-ionization laser spectroscopy technique. Spins for the ground states in 179,181,183Tl have been determined as I=1/2. Magnetic moments and changes in the nuclear mean-square charge radii have been deduced. By applying the additivity relation for magnetic moments of the odd-odd Tl nuclei the leading configuration assignments were confirmed. A deviation of magnetic moments for isomeric states in 182,184Tl from the trend of the heavier Tl nuclei is observed. The charge radii of the ground states of the isotopes 179-184Tl follow the trend for isotonic (spherical) lead nuclei. The noticeable difference in charge radii for ground and isomeric states of 183,184Tl has been observed, suggesting a larger deformation for the intruder-based 9/2− and 10− states compared to the ground states. An unexpected growth of the isomer shift for 183Tl has been found.
Die Zahlen 179-184 sind im Titel hochgestellt
Gesehen am 04.10.2018